Do we need to eradicate Helicobacter pylori in patients with GORD? - Masaoka, Tatsuhiro (SAGE Publications, 2013)
Eradication of Helicobacter pylori should not be avoided because of complicated reflux symptoms. Previously, although H. pylori eradication in patients with GORD was considered to induce unfavourable effects that worsen reflux symptoms, recent reports indicates that it can have favourable consequences by reducing symptoms and therefore improving quality of life, especially in GORD patients without severe corpus atrophy or severe hiatal herniation.